2014
DOI: 10.1021/cs401009z
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Enhanced Catalysis in Scaffolded Multienzyme Cascade Reactions

Abstract: New developments in nucleic acid nanotechnology and protein scaffold designs have enabled unparalleled control over the spatial organization of synthetic multienzyme cascade reactions. One of the goals of these new technologies is to create nanostructured enzyme cascade reactions that promote substrate channeling along the cascade and, in doing so, enhance cascade catalysis. The concept of substrate channeling has a long and rich history in biochemistry and has established methods of evaluation and quantificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 47 publications
2
114
0
1
Order By: Relevance
“…3 Enlightened by the natural cellular metabolism, a series of multienzyme conjugates were developed, and signicant enhancements in the cascade reaction kinetics and efficiency both in vivo and in vitro have been reported. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite the massive interests, the assembly of "in vivo" multienzyme architecture and its full understanding are always difficult due to the extreme complexity of the intracellular environment.…”
Section: Introductionmentioning
confidence: 99%
“…3 Enlightened by the natural cellular metabolism, a series of multienzyme conjugates were developed, and signicant enhancements in the cascade reaction kinetics and efficiency both in vivo and in vitro have been reported. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite the massive interests, the assembly of "in vivo" multienzyme architecture and its full understanding are always difficult due to the extreme complexity of the intracellular environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al used the sucrose oxidation enzymes discussed above to utilize DNA as a structural scaffold for altering the separation between sequential enzymes [19]. Although these studies have focused on proximity, non-bioelectrocatalytic studies have shown that substrate channeling is important [32]. Therefore, the future of enzyme cascade work will need to focus on developing synthetic metabolons that both provide proximity between active sites, and also provide for substrate channeling.…”
Section: Synthetic Metabolonsmentioning
confidence: 99%
“…On the other hand, these structural elements are also heterologous to the host organisma nd can contribute to the metabolicb urden.P reliminary design rules to control the number and orientation of enzymes in as patially nanostructured scaffold systemw ere clustered by Lin et al in three aspects:( i) inter-enzyme distance,( ii)a ctive site orientation,a nd (iii)m ultienzyme architecture. [134] During the last years,v arious innovative examples to create biomolecular nanostructures have been reported.T hese structures can be formed by proteinprotein interactions [135] as wella sn ucleic acids (DNA, [136] RNA [137] )o rp olymers (e.g.,c ell mimicking polymersomes [138] )( Figure 14). Theg roup of Keasling exemplified this approach by constructingaheterologous mevalonate pathway which contains hydroxyl-methylglutaryl-CoA synthase (HMGS)a nd hydroxyl-methylglutaryl-CoA reductase (HMGR)f rom S. cerevisiae)t ogether with the endogeneousa cetoactetyl-CoA transferase (AtoB)i nE.…”
Section: Assembling the Cast:scaffoldingmentioning
confidence: 99%